The manager's pocket guide to virtual teams - Bellingham, Richard (Managers Pocket Guide Series., 2001)
Learn how to handle the new opportunities and challenges when managing virtual teams that work in different locations and come from different disciplines, departments & emdash;even organizations. The book is full of fresh, new ways to overcome the unique and sometimes overwhelming barriers: How to create a forum for idea-sharing, solve problems among people from multiple functions, keep everyone in the "virtual loop," know when the team needs to meet in person vs. via technology, prevent things from slipping through the cracks, keep members up-to-date on changes and decisions, and much more. Exp